2020
DOI: 10.31557/apjcp.2020.21.3.733
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin For Decreasing Proliferative Marker in Women with Endometrial Cancer: A Randomized Double-blind Placebo-Controlled Trial

Abstract: However, women diagnosed with advanced-stage or recurrence disease have a very poor prognosis with a 5-year survival rate of below 50% (SEER, 2019). The increasing incidence of EC has been attributed to various factors, including obesity, diabetes, reproductive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…For hypoglycemia, metformin might be tolerated in patients with metastatic/recurrent breast cancer or those receiving adjuvant endocrine therapy, although no data were found in the neoadjuvant setting. Our findings were approximately consistent with previous studies 36,37 that reported that no patients with cancer who received metformin experienced SAEs, including hypoglycemia and lactic acidosis. Therefore, the addition of metformin to chemotherapy or endocrine therapy may be safe for use in patients with breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…For hypoglycemia, metformin might be tolerated in patients with metastatic/recurrent breast cancer or those receiving adjuvant endocrine therapy, although no data were found in the neoadjuvant setting. Our findings were approximately consistent with previous studies 36,37 that reported that no patients with cancer who received metformin experienced SAEs, including hypoglycemia and lactic acidosis. Therefore, the addition of metformin to chemotherapy or endocrine therapy may be safe for use in patients with breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…167 Taken together, metformin used in cancer therapy is one of the most successful cases of drug repurposing and several clinical trials, which have advanced to Phase III and Phase IV, are currently investigating the therapeutic potential of metformin in oral, prostate, breast, endometrial, and pancreatic cancers. [168][169][170][171] Disulfiram: Disulfiram was originally used in rubber vulcanization, but subsequently has been used for more than 60 years as an alcohol-aversion drug to treat alcohol abuse. 172,173 Mechanistically, disulfiram inhibits the activation of acetaldehyde dehydrogenase (ALDH), triggering severe nausea and vomiting symptoms contributing to abstinence.…”
Section: Non-oncology Drugs In Drug Repurposingmentioning
confidence: 99%
“…Nevertheless, a meta-analysis of the above studies supports a greater overall survival in metformin users compared to nonusers [ 133 ], although the low number of studies and the lack of randomized studies compromise the evidence level of the meta-analysis. Clinical trials using metformin for atypical endometrial hyperplasia (AEH) or EC have recently accumulated evidence for its efficacy [ 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. Most studies used the presurgical window approach, in which patients diagnosed by endometrial biopsy were treated with metformin during the period prior to hysterectomy, and some studies targeted patients who underwent fertility-sparing treatments in combination with progestins.…”
Section: What About Metformin? Is the Pi3k-akt Pathway A Target?mentioning
confidence: 99%